Tailor-made Ge-doped silica-glass for clinical diagnostic X-ray dosimetry - Alyahyawi, Amjad; Jupp, T.; Alkhorayef, M.; Bradley, David Andrew (Elsevier, 2018)
In the modern clinical practice of diagnostic radiology there is a growing demand for radiation dosimetry, it also being recognized that with increasing use of X-ray examinations additional population dose will result, accompanied by an additional albeit low potential for genetic consequences. At the doses typical of diagnostic radiology there is also a low statistical risk for cancer induction; in adhering to best practice, to be also implied is a low but non-negligible potential for deterministic sensitive organ responses, including in regard to the skin and eyes. Risk reduction is important, in line with the principle of ALARP, both in regard to staff and patients alike; for the latter modern practice is usually guided by Dose Reference Levels (DRL) while for the former and members of the public, legislated controls (supported by safe working practices) pertain. As such, effective, reliable and accurate means of dosimetry are required in support of these actions. Recent studies have shown that Ge-doped-silica glass fibres offer several advantages over the well-established phosphor-based TL dosimeters (TLD), including excellent sensitivity at diagnostic doses as demonstrated herein, low fading, good reproducibility and re-usability, as well as representing a water impervious, robust dosimetric system. In addition, these silica-based fibres show good linearity over a wide dynamic range of dose and dose-rate and are directionally independent. In the present study, we investigate tailor made doped-silica glass thermoluminescence (TL) for applications in medical diagnostic imaging dosimetry. The aim is to develop a dosimeter of sensitivity greater than that of the commonly used LiF (Mg,Ti) phosphor. We examine the ability of such doped glass media to detect the typically low levels of radiation in diagnostic applications (from fractions of a mGy through to several mGy or more), including, mammography and dental radiology, use being made of x-ray tubes located at the Royal Surrey County Hospital. We further examine dose-linearity, energy response and fading.